"y'+xy=y^2e^{x^2\/2}\\sin{x}"
divide both sides by "y^2"
"y'\/y^2+x\/y=e^{x^2\/2}\\sin{x}"
substitution: "t=1\/y"
"xt-t'=e^{x^2\/2}\\sin{x}"
let's solve first this equation: "xt-t'=0"
"\\int dt\/t=\\int xdx"
"\\ln{t}-\\ln{C}=x^2\/2"
"t=Ce^{x^2\/2}"
then solution to initial equation will have form: "t(x)=C(x)e^{x^2\/2}"
"t'(x)=C'(x)e^{x^2\/2}+xC(x)e^{x^2\/2}"
Let's put these to initial equation
"xC(x)e^{x^2\/2}-C'(x)e^{x^2\/2}-xC(x)e^{x^2\/2}=e^{x^2\/2}\\sin{x}"
"C'(x)=-\\sin{x}"
"C(x)=\\int -\\sin{x}dx=C_1+\\cos{x}"
then "t(x)=(C_1+\\cos{x})e^{x^2\/2}"
"y=1\/t=e^{-x^2\/2}\/(C_1+\\cos{x})"
Comments
Leave a comment